Acordo de não persecução penal: análise da viabilidade da derivação para a justiça restaurativa - Cavalcante, Elaine Cristina Monteiro (2022)
This dissertation has the scope to analyze the feasibility of the derivation of the non-prosecution agreement for restorative justice, bringing to light its foundations, its advantages and the appropriate procedure. The foundations of this feasibility , beyond the national and international normatives, rest on the notion of human dignity in its communicative and relational dimension, as well as on the notion of dignity as a limit and task of the State, since in the restorative procedure the equal human dignity of the other is recognized, once all are part of a community, where they are imposed limits to threats that may violate the dignity of those involved, emphasizing the responsibility of the State to protect the dignity of all, by confronting violence, the burden of which it has not been satisfactorily conducted. Given the global trend of expanding consensual or negotiated solutions, the non-prosecution agreement was introduced in our legislation, provided for in art. 28-A, of the Criminal Procedure Code, which consists of a procedural legal transaction, which takes place in the pre-procedural phase, according to which, by means of confession and acceptance of the investigated and his defender about the fulfillment of some conditions agreed with the Public Ministry, it is agreed not to file a criminal action against him, in such a way that the agreement is judicially approved, and once the established conditions are met, the agent's punishment is declared to be extinguished. The nonprosecution agreement is part of the consensual justice microsystem embodied in the Law of Special Criminal Courts, since its legitimation grounds are the same. Thus, it is feasible for the member of the Public Ministry to make the derivation of the non-prosecution agreement for restorative justice, once the requirements of art. 28-A, of the Criminal Procedure Code, using the permissive contained in art. 28-A, V, of the same legal diploma, which provides for the possibility of establishing compliance, for a determined period, with another condition, proportional and compatible with the criminal offense charged, exclusively, since restorative justice consists of a model differentiated within the consensual model of criminal dispute resolution. This derivation allows that cases selected by the member of the Public Ministry have a consensual solution, based on restorative principles and values, compatible and proportional to the criminal offense committed, which can decisively contribute to social pacification, reduction of crime and recidivism rates, once the causes and consequences of the criminal offense are understood, by means of repairing the damage caused, by holding the offenders and co-responsible once, providing the social restoration of the offender and the restoration of his ties with society and the State, enhancing the efficiency of the non-prosecution agreement, since the paradigm of the restorative justice invigorates the fundamental rights and guarantees of the parties, insofar as it strengthens the correct application of the fundamental principle of human dignity, which guides the Democratic State of Law